Spatial and temporal evolution of tourism flows among 296 Chinese cities in the context of COVID-19: a study based on Baidu Index - Yibo Tang; Gangmin Weng; Simeng Qin; Yue Pan (Humanities & Social Sciences Communications)
Abstract COVID-19 repeated outbreaks in China have significantly impacted residents’ lives, particularly in the tourism sector. Accurately assessing the spatio-temporal evolution of tourism flow under the disturbance of COVID-19 is essential for scientific tourism planning and management. This study analyzes the tourism information search index of 296 cities in China to represent tourist flow tendencies and explores the distribution characteristics and formation reasons of tourism flow from both tourist source and destination perspectives. The results are as follows. (1) The COVID-19 has severely affected Chinese tourists’ willingness to travel, with a decline of over 50% from 2020 to 2022 compared to 2019. Although a rebound is observed in 2023, it has not yet returned to pre-epidemic levels. (2) COVID-19 has impacted the spatial distribution pattern without altering the essential characteristic of “high in the East and low in the West.” The distribution of core tourist sources is “bow-shaped”, while that of popular destinations is “U-shaped”. (3) In both tourism information inflow and outflow, the number of “head” and “tail” cities is relatively small, with most cities situated in the “middle” echelon. Additionally, the “Matthew effect” has emerged among tourist destination cities, which may aggravate the unbalanced nature of tourism distribution in China. Therefore, future tourism development should be strategically planned, respecting the principles of evolutionary patterns.